Analisis Swot Potensi Wisata Pantai Desa Rumbia Kecamatan Langowan Selatan Kabupaten Minahasa - Supriyanto Supriyanto; Pebisitona Mesajaya Purba; Cristofer Sumiok (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The tourism sector is one of the most important sectors in a country's development because it contributes to job creation, government revenue, and increased national welfare. Rumbia beach has an attractive natural charm, but this does not get a response in line with tourist visits, both foreign tourists and domestic tourists. This research examines how strategies in developing beach tourism areas located in Rumbia Village, Minahasa Regency, North Sulawesi Province. The qualitative data analysis technique in this research is the SWOT analysis approach. The results of this study show that Rumbia Beach has great potential to be developed as a tourist attraction. This is supported by the unspoiled natural beauty, relatively easy access, and the existence of several interesting photo spots. However, there are still some weaknesses and threats that need to be considered. These weaknesses include the lack of infrastructure and tourist support facilities, lack of promotion and publication, and lack of variety of tourist activities.